Effect of Anogeissus leiocarpus Guill and Perr Leaf on Hyperglycaemia and Associated Dyslipidaemia in Alloxan-induced Diabetic Rats - Onoja, Uwakwe S; Ugwu, Cynthia C; Uzor, Philip F; Nweze, Innocent E; Omeje, Edwin O; Nnamani, Petra O; Nwachukwu, Ekere; Njoku, Ivoke; Effiong, Eyo J (Dhaka University Journal of Pharmaceutical Sciences, 2018)
People living with diabetes mellitus across the world are expected to rise to 592 million by 2035 and the pandemic disease is worst in the developing countries like Nigeria, where the cost of treating/managing diabetes mellitus is relatively out of the reach of many diabetic patients. The study investigated the effect of Anogeissus leiocarpus Guill and Perr ethanolic leaf extract on blood glucose and other biochemical indices in alloxan-induced diabetic adult male Wistar albino rats. Diabetes mellitus was induced in overnight-fasted rats by a single intraperitoneal injection of alloxan monohydrate (150 mg/kg body weight). Diabetic rats were then treated with the extract for 14 days. Blood glucose, lipid profile and liver glycogen levels were determined. After the treatment with the extract, the fasting blood glucose levels significantly reduced (p < 0.05) in treated diabetic rats (62.2 ± 18.4 mg/dl) compared to untreated diabetic rats (73.8± 8.2 mg/dl). There was also significant (p < 0.05) reduction in the hyperlipidemic parameters. The results revealed that A. leiocarpus ethanolic extract has antidiabetic and hypolipidemic effects in alloxan-induced diabetic rats. Dhaka Univ. J. Pharm. Sci. 17(1): 65-72, 2018 (June)